Efficacy and safety of tirzepatide in patients with type 2 diabetes: A systematic review and meta-analysis - Tang, Yan; Zhang, Lin; Zeng, Yuping; Wang, Xia; Zhang, Mei (Frontiers in Pharmacology, 2022)
Purpose: A systematic review and meta-analysis was conducted to combine the data available from clinical trials and evaluate the clinical efficacy and safety of tirzepatide in people with Type 2 Diabetes (T2D). Methods: We systematically searched the MEDLINE, Embase, Cochrane Library and Clinical trial registries (https://clinicaltrials.gov) up to March 25, 2022 for randomized controlled trials (RCTs) that compared tirzepatide with placebo or active hypoglycemic drugs in subjects with T2D. Heterogeneity was judged by the I2 value and Cochran's Q test. The randomized effects model was adopted to calculate risk ratios and weighted mean differences (WMD). The primary outcome was the change from baseline in HbA1c levels. Secondary efficacy endpoints were fasting serum glucose (FSG), change of body weight, blood pressure, fasting lipid profiles and safety indexes. Results: Six trials comprising 6579 subjects (4410 in tirzepatide and 2054 in control group) fulfilled the prespecified criteria and were included. Tirzepatide treatment resulted in reducing HbA1c (WMD: -1.07%; 95% confidence intervals [CI]: -1.44, -0.56), FSG (WMD, -21.50mg/dL; 95% CI: -34.44, -8.56), body weight (WMD: -7.99 kg; 95% CI -11.36, -4.62) and blood pressure, ameliorated fasting lipid profiles, without increasing hypoglycemia, either as monotherapy or an add-on therapy. Tirzepatide increased the risk of gastrointestinal adverse events mainly in add-on therapy, but not in terms of pancreatitis or cholelithiasis. Furthermore, tirzepatide presented dose-response effect on reduction in HbA1c and body weight, increase in nausea and vomiting. Conclusions: In patients with type 2 diabetes, tirzepatide shows superior blood glucose control, weight loss performance, without increased risk of hypoglycemia.